Relapsing Polychondritis with a Cobble-stone Appearance of the Tracheal Mucosa, Preceded by Posterior Reversible Encephalopathy Syndrome - Ikeda, Takahide (Intern Med, 2020)
A 25-year-old woman had convulsions and disturbance of consciousness. Head magnetic resonance imaging (MRI) showed punctate areas in the occipital lobes with increased signals on T2-weighted imaging. The MRI abnormalities responded well to steroid pulse therapy, so we made a diagnosis of posterior reversible encephalopathy syndrome (PRES). Three months later, she developed a fever and dyspnea. Chest computed tomography revealed marked thickness of the tracheal and bronchial wall, and bronchoscopy showed a cobble-stone appearance of the tracheal mucosa, indicative of relapsing polychondritis (RPC). We consider that PRES had developed due to autoimmune vasculitis in the brain with RPC.